Fashionably sustainable: extending the theory of planned behavior to predict intentions to purchase second-hand clothes - Sharma, Harshita; Arya, Bhavana; Bisht, Vandana; Kumar, Harshita (Frontiers in Sustainability, 2025)
Fashion production, largely driven by the demand for fashion, is a major contributor to environmental degradation. With the rising awareness of the consequences of fashion consumption, consuming second-hand fashion is a fast-emerging strategy. The current study utilises Theory of Planned Behavior (TPB) framework to investigate the intentions to purchase second-hand clothes in young Indian consumers. TPB is extended by adding mindful consumption and environmental concern as predictors of attitude towards second-hand clothes. 222 Indian young adults (18–30 years) participated in the research and data were analysed using Structural Equation Modelling (SEM). Environmental concern emerged as the most significant predictor of a positive attitude towards second-hand clothing, followed by mindful consumption. Attitude, in turn, had the strongest influence on purchase intention, while subjective norms and perceived behavioral control also showed significant positive effects. The tested model was significant and explained 46.5% variance in purchase intentions. This research contributes to sustainability literature by validating the extended TPB model in the context of second-hand fashion in India.